2011
DOI: 10.1371/journal.pone.0027273
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Enteral Feeding in Cerebral Malaria in Resource-Poor Settings: A Randomized Trial

Abstract: BackgroundEarly start of enteral feeding is an established treatment strategy in intubated patients in intensive care since it reduces invasive bacterial infections and length of hospital stay. There is equipoise whether early enteral feeding is also beneficial in non-intubated patients with cerebral malaria in resource poor settings. We hypothesized that the risk of aspiration pneumonia might outweigh the potential benefits of earlier recovery and prevention of hypoglycaemia.Method and FindingsA randomized tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 24 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…Serial GCS (assessed 6 hourly) and lactate (assessed 6 hourly) data from adult patients with severe malaria enrolled in studies at Chittagong Medical College Hospital (CMCH), Chittagong, Bangladesh between 2005 and 2012. The Bangladeshi patients were enrolled in observational and treatment studies including studies on levamisole, timing of enteral feeding, N-acetylcysteine and paracetamol [15, 18, 20, 22]. These randomized clinical trials were monitored internally as well as by an outside monitor.…”
Section: Methodsmentioning
confidence: 99%
“…Serial GCS (assessed 6 hourly) and lactate (assessed 6 hourly) data from adult patients with severe malaria enrolled in studies at Chittagong Medical College Hospital (CMCH), Chittagong, Bangladesh between 2005 and 2012. The Bangladeshi patients were enrolled in observational and treatment studies including studies on levamisole, timing of enteral feeding, N-acetylcysteine and paracetamol [15, 18, 20, 22]. These randomized clinical trials were monitored internally as well as by an outside monitor.…”
Section: Methodsmentioning
confidence: 99%
“…Given their low incidence, our trial was underpowered to demonstrate with certainty that implementation of the infection treatment bundle did not result in more adverse events. This conclusion is important because previous sepsis therapies supported by scientific evidence from high-income countries resulted in more complications and/or higher fatality rates when implemented in resource-limited settings [7][8][9]. For instance, three randomized controlled trials conducted in sub-Saharan Africa reported increased mortality associated with early fluid resuscitation in patients with sepsis and malaria in the absence of mechanical ventilation [8,9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of the 7 million global deaths in neonates and infants annually are attributable to infection, with the majority of cases occurring in middle-and low-income countries [4]. Recommended intensive care interventions for the management of patients with sepsis [5] may be impractical, unaffordable, and possibly even harmful when implemented in middle-and low-income countries [6][7][8][9]. Consequently, early recognition and appropriate treatment of acute infection is essential.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical trial of children and adults with CM compared the effect of early and late commencement of enteral feeds in a setting where intubation was not available [68]. Early enteral feeding was started on the day of admission, while late enteral feeding was begun after 60 h in adults or 36 h in children [68]. The trial was stopped after 56 subjects were enrolled owing to a high rate of aspiration pneumonia in the early feeding group.…”
Section: Nutritional Supportmentioning
confidence: 99%